The development and validation of Malaysian- Based Basic and integrated science process skills inventory (MB-BISPSI) - Ong Eng Tek, Md Yassin Sopia, Baharom Sadiah, Yahaya Asmayati, Mat Said Zahid (Universiti Pendidikan Sultan Idris, 2011)
The development and validation of Malaysian- Based Basic and integrated science process skills inventory (MB-BISPSI) by Ong Eng Tek, Md Yassin Sopia, Baharom Sadiah, Yahaya Asmayati, Mat Said Zahid,